Józef Kozielecki - nauczyciel akademicki i twórca psychotransgresjonizmu. Autobiografia w literackich i edukacyjnych kontekstach = Józef Kozielecki - a scholar and creator of psychotransgression approach. The autobiography through literary and educational contexts - Seul, Anastazja (1961- ) (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article presents this Polish psychologist as a belles-lettres lover. It portrays a professor who did use not only literary works during his lectures but also wrote such texts on his own. The article points out that his autobiography contains direct or modified quotes, paraphrases, and references to literary achievements.
Keywords: Kozielecki, Józef (1936-2017); psychotransgresjonizm; rozwój osobisty; kultura literacka; aksjologia; psychotransgressionism; personal development; literary culture; axiology